Selective hydrogenolysis of catechyl lignin into propenylcatechol over an atomically dispersed ruthenium catalyst - Shuizhong Wang (Nature Portfolio, 2021)
C-lignin represents an ideal feedstock for producing catechol derivatives. Here, the authors engineered an atomically dispersed Ru catalyst, which can cleave C−O bonds efficiently and circumvent C=C bonds hydrogenation selectively, thus leading to propenylcatechol in high yields with high TONs.